Assessment and Enhancement of Coastal Community Resilience Strategies: A Case Study of Wuyuan Bay in Xiamen - Xu Mengjie; Liu Xingzhao; Xie Huili; Zhang Yang; Dai Hongxia; Zhou Yanhai; Huang Faming (Redai dili)
Amidst the intensifying global climate change, coastal cities face multiple marine disaster threats due to sea level rise and frequent extreme weather events. Storm surge-induced flood disasters and their secondary effects (e.g., urban waterlogging) pose systemic risks to the lives of the residents, properties, and coastal system infrastructure. Compared with traditional disaster prevention models, the synergistic mechanism between resilience theory and community risk management not only provides a theoretical framework for urban complex risk prevention, but also demonstrates dynamic adaptive advantages in pre-disaster prevention, disaster response, and post-disaster recovery. Accordingly, this study integrated the resilience community theory with the sponge city concept, selecting 25 storm surge-prone bay communities in the Xiamen Wuyuan Bay Area as samples to establish a community resilience evaluation framework encompassing exposure, vulnerability, adaptability, and spatial connectivity. By integrating 16 subjective and objective indicators, including the rescue facility coverage rate and residents' disaster preparedness literacy, we employed the AHP-CRITIC combined weighting method to determine indicator weights and quantify community resilience levels using TOPSIS analysis. The key findings are categorized as follows: (1) an overview of the marine disaster context, the theoretical evolution of resilient communities, and existing research gaps. The literature review indicated that marine disaster threats to coastal urban safety showed significant upward trends, where communities, as direct disaster-bearing entities, needed urgent refined resilience assessments considering their spatial heterogeneity and component vulnerability. International practice comparisons revealed three critical deficiencies in China's resilient community development: overreliance on infrastructure hardware while neglecting the landscape spatial resilience layout, insufficient innovation in social organizational resilience and collaborative mechanisms, and superficial resident participation lacking substantive interactive mechanisms. (2) Development of multidimensional resilience evaluation system Through meta-analysis and expert consultation, we established a dual-dimensional ("vulnerability-adaptability") evaluation system comprising 7 primary and 16 secondary indicators. The AHP-CRITIC combined weighting results indicated that hazard level (0.221), disaster prevention capacity (0.169), and emergency response capacity (0.168) constituted the highest-weighted primary indicators. Secondary indicators, including coastal length, shoreline protection intensity, and volunteer rescue station accessibility, demonstrated significant spatial exposure and emergency response weights, suggesting for their prioritization in coastal community retrofitting. (3) Implementation of a resilience assessment system for coastal community in Wuyuan Bay Field surveys and questionnaire data enabled quantitative resilience analysis of 25 communities. TOPSIS results revealed geographical location and residents' disaster preparedness as core drivers of resilience differentiation. Inner bay communities (e.g., D25) achieved maximum resilience (0.872) through wetland regulation, natural terrain barriers, and emergency facility clusters, whereas outer bay communities (e.g., D1) showed minimal resilience (0.312), owing to high-risk exposure and medical resource scarcity. Wetland ecosystems notably reduced drainage system loads through hydrological regulation and flood detention mechanisms. (4) Optimization strategies for coastal community resilience. This study systematically identified the core elements for developing community resilience during flood-related disasters through the establishment of a coastal community resilience assessment system and empirical research. Through a comparative analysis of typical domestic and international scenarios, we proposed an actionable resilience enhancement strategy system. For public space optimization, dual-purpose strategies for both normal and emergency conditions were emphasized for road networks and green systems, integrating traffic management with ecological protection. For ecological water system development, the water conservation mechanisms of coastal wetland ecological barriers were systematically elucidated, and a synergistic optimization pathway for wetland protection and community water systems based on nature-based solutions was proposed. Regarding emergency shelter spatial planning, an innovative comprehensive evaluation framework was established, incorporating location accessibility, per capita shelter area thresholds, disaster prevention facility standards, and emergency transportation systems. For social governance, resident participation mechanisms and smart management platforms were suggested to amplify community resilience through flexible interaction and resource integration.